1994
DOI: 10.21273/jashs.119.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Drought Tolerance of Viburnum plicatum var. tomentosum `Mariesii' in Pine Bark-amended Soil

Abstract: Container-grown Viburnum plicatum Thunb. var. tomentosum (Thunb.) Miq. `Mariesii' were planted in unamended planting holes, tilled plots, and tilled plots amended with aged pine bark. A 36-day drought was initiated 108 days after planting. Amending induced N deficiencies, reduced shoot growth, and increased root growth. Plants harvested from tilled and planting-hole plots at drought initiation had 63% and 68% more dry weight, respectively, than plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Enhanced root establishment and transplant survival. Numerous studies have demonstrated that improved water retention and reduced weed growth are correlated with increased root growth and exploration by desirable plants (39,138). Mulches allow roots of trees and shrubs to extend and establish far beyond the trunk compared to bare soil (17,134) and thus become increasingly stabilized.…”
Section: Viewpointmentioning
confidence: 99%
“…Enhanced root establishment and transplant survival. Numerous studies have demonstrated that improved water retention and reduced weed growth are correlated with increased root growth and exploration by desirable plants (39,138). Mulches allow roots of trees and shrubs to extend and establish far beyond the trunk compared to bare soil (17,134) and thus become increasingly stabilized.…”
Section: Viewpointmentioning
confidence: 99%
“…In contrast, root mass ratio and root to shoot ratio were significantly developed in the seedlings that mulched compared with those non-mulched. Several studies have proved that enhanced water preservation and weed competition decreased as happened in mulched positions are correlated with improved root growth by desirable plants (Fausett and Rom., 2001;Wood et al, 1994). Mulches permit roots of plant to spread and establish far beyond the stem compared to non-mulched (bare) soil (Burgess et al, 1997) and consequently become gradually stabilized.…”
Section: Results Of Mulching Treatments In Tablementioning
confidence: 99%
“…Temperature modification is extremely important near the soil surface as hot or cold surface soils can kill new transplants that have not had time to generate a large root mass and establish into deeper, more moderate, surrounding soils [19]. Numerous studies have demonstrated that improved water retention and reduced weed growth are correlated with increased root growth and exploration by desirable plants [30,31]. Hence, mulches allow roots of trees to extend and establish far beyond the trunk compared to bare soil and thus become increasingly stabilized [32,33].…”
Section: Organic Mulchingmentioning
confidence: 99%